Acute Obstructive Hydrocephalus: An Unusual Complication after Cardiopulmonary Bypass - Gonzlez-Santos, J. M.; Gonzlez-Santos, M. L.; Vallejo, J. L. (The Thoracic and Cardiovascular Surgeon, 1986)
A case of acute obstructive hydrocephalus in a patient undergoing an aortic valve replacement is presented. This condition came about as a result of massive left cerebellar hemisphere infarction, probably due to a calcific embolism from the aortic valve. The cerebrospinal fluid circulation was blocked by compression of the fourth ventricle and the Sylvius aqueduct secondary to ischemic edema. Following external ventricular drainage, the hydrocephalus resolved but a neurological deficit secondary to the cerebellar and brain stem infarction became evident. The diagnostic, prognostic and therapeutic implications of this unusual complication following cardiac surgery are discussed.
Keywords: Cardiopulmonary bypass; Cerebellar infarction; Hydrocephalus